Molecular identification and antimicrobial susceptibility of Nocardia spp. isolated from bovine mastitis in Brazil - Condas, Larissa A.Z.; Ribeiro, Márcio Garcia [UNESP]; Yazawa, Katsukiyo; de Vargas, Agueda P. Castagna; Salerno, Tatiana; Giuffrida, Rogério; Langoni, Hélio [UNESP]; Melville, Priscila A.; Biesdorf, Sônia; Matsuzawa, Tetsuhiro; Gonoi, Tohru; Kastelic, John P.; et al. (Elsevier, 2013)
Nocardia spp. infections can cause severe damage to the mammary gland due to suppurative pyogranulomatous lesions and lack of clinical cure in response to conventional antimicrobial therapy. Although Nocardia infections are considered relatively uncommon in cows, there has been an apparent worldwide increase in the incidence of bovine mastitis caused by Nocardia spp, perhaps due to environmental transmission of this ubiquitous pathogen. The objectives of present study were to determine: (i) species distribution of 80 Nocardia isolates involved in bovine mastitis (based on molecular methods); and (ii) antimicrobial susceptibility pattern of all isolates from three geographical areas in Brazil. In this study, Nocardia nova (80%) was the most frequently isolated species, followed by Nocardia farcinica (9%). Additionally, Nocardia puris, Nocardia cyriacigeorgica, Nocardia veterana, Nocardia africana, and Nocardia arthritidis were detected using 16S rRNA sequencing. This is apparently the first report of N. puris, N. veterana, N. cyriacigeorgica, N. arthritidis and N. africana in association with bovine mastitis. Based on the disk diffusion test, isolates were most frequently resistant to cloxacillin (75%), ampicillin (55%) and cefoperazone (47%), whereas few Nocardia spp. were resistant to amikacin, cefuroxime or gentamicin. © 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial resistance; Bovine mastitis; Brazil; Molecular identification; Nocardia